The student feedback literacy instrument (SFLI): multilingual validation and introduction of a short-form version - Weidlich, Joshua; Jivet, I.; Woitt, Svenja; Orhan Göksün, D.; Kraus, J.; Drachsler, H. (Assessment & evaluation in higher education, 2025)
Feedback literacy is gaining recognition as a key concept for understanding how engage with and learn from feedback in higher education. This study presents validity evidence for a refined version of the Student Feedback Literacy Instrument (SFLI), designed to measure the construct across two dimensions—feedback attitudes and feedback practices—in German, English, and Turkish. We developed both a full-length and a short-form version (SFLI-S). Using confirmatory factor analyses on different student samples (Ntotal= 1424), we confirmed the two-factor structure across languages, supporting the model of feedback literacy comprising of attitudinal and behavioral components. Associations with related constructs further support the instrument’s convergent validity. As a psychometrically sound, multilingual instrument, the SFLI can facilitate cross-cultural feedback literacy research and provide a valuable tool for research and educational practice. The SFLI-S offers an economical alternative, enabling wider integration into studies on how students engage with feedback.
Gesehen am 18.08.2025